Double sites doping local chemistry Adjustment: A Multiple-Layer oriented P2-Type cathode with Long-life and Water/Air stability for sodium ion batteries - Ouyang, Baixue; Chen, Tao; Liu, Xichang; Zhang, Mengjie; Liu, Penggao; Li, Puliang; Liu, Weifang; Liu, Kaiyu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
•A double site doped layered P2-K0.05Na0.62Mn0.6Ni0.3Cu0.1O2 cathode is designed.•The expanded layer spacing of K doping provides a higher electrochemical capacity.•A combined analysis of first-principles calculation simulation and experimental verification.•The regulation of cycling stability by setting the cut-off voltage are provided.•It shows excellent cycling performance and environmental exposed stability. P2-type Ni/Mn layered oxides have attracted intensive interest as a kind of promising cathode materials because of their high specific capacities and unique 2D Na+ diffusion path. However, the poor stability and irreversible phase transition at high voltage during charge and discharge process greatly hinders its practical applications. Herein, a novel double site substitution strategy is reported that large-sized K+ is riveted in the prismatic Na+ sites and Cu2+ is occupies in the transition metal sites. The K+ doping lead to the lattice expansion along c-axis, which facilitating sodium ions transport. In addition, the double sites substitution improves the stability of the materials exposed in air and water environments. A combined analysis of first-principles calculation simulation and experimental verification determining that larger interlayer spacing decreases the diffusion barrier of sodium ions. The as-prepared multiple-layer oriented P2-K0.05Na0.67Mn0.6Ni0.3Cu0.1O2 shows excellent rate performance, fast sodium ion transport ability and superior cycling performance with a high-capacity retention of 91.2 % at a high current density of 1 A g−1 after 1800th cycles. Therefore, this work provides a new insight for the design of stable and high-performance cathode materials for sodium ion batteries.